Optimising mechanical properties of basalt fibre thermoplastic composite through alteration of processing conditions - Lim, Nicholas Jun Ji (Nanyang Technological University, 2020)
The overall purpose of the present study is to evaluate the feasibility of basalt fibres as a sustainable alternative for composite materials, with a focus on material and processing study on regional basalt fibre for local industrial adoption. In this study, the problems investigated include optimisation of process parameters of basalt fibre fabrics with different thermoplastic matrices, the effect of compatibiliser, and the effect of composite layup on their mechanical properties. The composites were produced using compression moulding process, water jet cut to suitable sizes with mechanical properties tested using an Instron machine and fibre-matrix interaction analysed using microscope imaging. Unidirectional (UD) basalt fibre polycarbonate (PC) composite achieved the highest ultimate tensile strength (UTS) of 669 ± 65.1 MPa and flexural strength of 629 ± 108 MPa. The specimen containing fibre lay up [0/T/90/90/T/0] with PC as the matrix had superior matrix impregnation and least porosity when analysed under the microscope. The addition of compatibiliser, maleic-anhydride-polypropylene (MAPP) has improved the adhesion of polypropylene (PP) on the basalt fibre (BF) fabric, observed using Field Emission Scanning Electron Microscope (FESEM). Despite this, mechanical properties of laminate with MAPP added showed lower normalised mechanical strength compared the laminate with no MAPP added. Mixed fibre orientations in a specimen was observed to reduce the number of voids and improves impregnation, at the cost of tensile and flexural strength of the specimen. From the wide range of parameters tested, mechanical properties of composites are affected by many factors and it is unlikely that a specimen will be superior in all factors. Depending on the application of the specimen, compromises should be made.